Prevalence and factors associated with depression, anxiety and stress among healthcare workers of Trinidad and Tobago during COVID-19 pandemic: a cross-sectional study - Koomatie Ramsaroop; B Shivananda Nayak; Pradeep Kumar Sahu; Shivanand Maharaj; William Mootoo; Sharaz Khan; Rian Marie Extavour (BMJ Open)
Objectives To determine the prevalence and factors associated with depression, anxiety and stress among healthcare workers (HCWs) during COVID-19 pandemic.Design Cross-sectional online survey.Setting HCWs from four major hospitals within the Regional Health Authorities of Trinidad and Tobago.Participants 395 HCWs aged ≥18 years.Main outcome measures Depression, anxiety and stress scores.Results Among the 395 HCWs, 42.28%, 56.2% and 17.97% were found to have depression, anxiety and stress, respectively. In the final stepwise regression model, contact with patients with confirmed COVID-19, p<0.001 (95% CI 3.072 to 6.781) was reported as significant predictors of depression. Further, gender, p<0.001 (95% CI 2.152 to 5.427) and marital status, p<0.001 (95% CI 1.322 to 4.270) of the HCWs were considered to be correlated with anxiety. HCWs who had contact with patients with suspected COVID-19 had lower depression, p<0.001 (95% CI −5.233 to −1.692) and stress, p<0.001 (95% CI −5.364 to −1.591).Conclusions This study has depicted the prevalence and evidence of depression, anxiety and stress among HCWs during the COVID-19 pandemic. The findings of the study will serve as supportive evidence for the timely implementation of further planning of preventative mental health services by the Ministry of Health, for frontline workers within the public and private health sectors.